TATALAKSANA STENTING PADA CAROTID ARTERY DISEASE SERTA PEMANTAUANNYA : SERIAL KASUS - Gilbert Tangkudung; David Wyanto; Mieke A.H.N Kembuan (Jurnal Sinaps, 2020)
Stroke is one of the leading causes of morbidity and mortality.1 According to Riskesdas there is an increase of stroke incidence ranging from 7 per 1000 population in 2013 to 10.9 per 1000 population in 2018.2 Extracranial internal carotid artery stenosis accounts for about 10-15% of ischemic strokes.3Case 1, 51 years old male came with chief complaint of recurrent weakness of his right extremities. Physical examination revealed right hemiparesis with NIHSS score of 3. Brain CT scan showed multiple lacunar infarcts. Angiography results showed intracranial atheroscleroris lesions of the right internal carotid artery, bifurcation of the left internal carotid artery and left verterbralis artery.Case 2, 57 years old woman came with chief complaint of weakness in her left extremities. Physical examination showed left hemiparesis with NIHSS score of 1. Brain MRI and MRA revealed multiple chronic infarcts and thrombus in the right and left external carotid arteries. Angiography results showed a stenotic lesion in the left internal carotid bifurcation.Revascularization measures were taken to reduce the risk of developing further ischemia. Both patients had recurrent one-sided weakness and treated with carotid artery stenting (CAS), pharmacotherapy and lifestyle modification. After CAS the patient did not complain of recurrent weakness and carotid doppler results revealed no restenosis.